The Provision of Dowry in Iranian Civil Law according to Imamiyah School - Hidayah, Okti Nur Hidayah (Jurnal Syariah dan Hukum Komparatif, 2023)
In Iranian wedding tradition, the dowry (mahr) is not paid upfront as done in Arab culture, and there is no set deadline for its payment. The regulations regarding dowry in Iran are outlined in the Civil Code of the Islamic Republic of Iran, which states that anything that can be considered property, owned, and controlled can be designated as dowry. In the subsequent article, it is explained that dowry can be entirely or partially deferred. This article aims to elucidate the concept of deferred dowry (mahar dihutang) in Iranian civil law from the perspective of the Imamiyah School of Thought, which is the predominant school of thought in Iran. This study is conducted through a literature review with a normative approach. The research findings reveal that items eligible to be considered as dowry are those with an associated market value, in alignment with the principles of the Imamiyah school. Deferred dowry is permitted within the Imamiyah school, but when the husband is incapable of paying the dowry, the wife is allowed to make a decision to abstain from conjugal relations with him. This, however, cannot be used as a reason for divorce. In Iran, there exists a phenomenon known as "mahar prisoner" for husbands who fail to pay the dowry in full after marriage.